A Pediatric Infectious Diseases Perspective of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) and Novel Coronavirus Disease 2019 (COVID-19) in Children. (25th August 2020) - Shane, Andi L; Sato, Alice I; Kao, Carol; Adler-Shohet, Felice C; Vora, Surabhi B; Auletta, Jeffery J; Nachman, Sharon; Raabe, Vanessa N; Inagaki, Kengo; Akinboyo, Ibukunoluwa C; Woods, Charles; Alsulami, Abdulsalam O; et al.
Abstract: Understanding the role that children play in the clinical burden and propagation of severe acute respiratory syndrome coronavirus 2, responsible for coronavirus disease 2019 (COVID-19) infections, is emerging. While the severe manifestations and acute clinical burden of COVID-19 have largely spared children compared with adults, understanding the epidemiology, clinical presentation, diagnostics, management, and prevention opportunities and the social and behavioral impacts on child health is vital. Foremost is clarifying the contribution of asymptomatic and mild infections to transmission within the household and community and the clinical and epidemiologic significance of uncommon severe post-infectious complications. Here, we summarize the current knowledge, identify resources, and outline research opportunities. Pediatric infectious diseases clinicians have a unique opportunity to advocate for the inclusion of children in epidemiological, clinical, treatment, and prevention studies to optimize their care as well as to represent children in the development of guidance and policy during pandemic response. Abstract : We review current knowledge, epidemiology, clinical presentation, diagnostics, management, prevention, and preparedness for children with severe acute respiratory syndrome coronavirus 2 infections, listing resources, outlining research opportunities, and advocating for the unique needs of children in coronavirus 2019 pandemic response.